운영 효율성을 고려한 감염병 전문병원의 일반병동 건축계획에 관한 연구 - 한은비; 권순정 (의료·복지 건축, 2021)
Purpose: As the need for a hospital specializing in infectious diseases has increased, construction is being promoted. Hospitals specializing in infectious diseases receive some state subsidies, but in the case of private hospitals, hospital operation efficiency should be considered to prevent cost loss. Therefore, we aim to derive a building plan for a general ward in a hospital specializing in infectious diseases that can be used not only in normal times but also in times of crisis. Methods: In this study, relevant literature review and field interviews were conducted with medical staff working in facilities designated as infectious disease hospitals. Results: The general ward building plan of the hospital specializing in infectious diseases was classified into three categories and presented. 'Spatial composition' for nursing unit and ward zoning, 'Spatial plan' for ward space conversion in normal times and crises, 'Bedroom plan' for effective dimensions and area of the ward. Implications: It can be used as a guideline when designing an infection-facility ward. And it can be a basis for inducing improvements to prevent infection in the ward of existing medical facilities.
Keywords: Infection diseases hospital; General ward; Normal and Crisis; Space conversion plan; 감염병 전문병원; 일반병동; 평시 및 위기 시; 공간전환계획